Dampak Gaya Hidup Terhadap Kepuasan Konsumen Dan Niat Membeli Kembali - Fadhlillah, Il; Handayani, Ririn; Nasution, Nurliana (CV. ITTC INDONESIA, 2024)
This study uses a quantitative method with a descriptive and explanatory survey approach. The study was conducted at Arifin Ahmad Pekanbaru Hospital, with the aim of testing the role of consumer satisfaction in mediating the influence of lifestyle on repurchase intentions. The population of this study were all directors, general managers, medical support managers, PPI (infection control center), purchasing, pharmacy, and users (doctors, nurses and midwives) totaling 120 people. Because the population members numbered 120 people, this study used a saturated sample method, meaning that all populations were sampled. All respondents will be used to obtain primary data related to the variables,. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. The results showed that lifestyle had a significant positive effect on repurchase intentions, lifestyle had a significant positive effect on consumer satisfaction, consumer satisfaction had a significant positive effect on repurchase intentions, and consumer satisfaction mediated the influence of lifestyle on repurchase intentions